2009
DOI: 10.1057/bm.2008.51
|View full text |Cite
|
Sign up to set email alerts
|

The specificity of luxury management: Turning marketing upside down

Abstract: International audienceToday luxury is everywhere. Everybody wants his products to be luxury. The concept of luxury is attractive and fashionable. There are luxury columns in all magazines and journals. There are TV shows on the business of luxury, and on luxury products and services. Even mass-consumption brands name many of their models " Deluxe" or qualify their experience as luxurious. New words have been recently invented and promoted that add to the complexity: masstige, opuluxe, premium, ultra-premium, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
324
1
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 480 publications
(371 citation statements)
references
References 3 publications
4
324
1
12
Order By: Relevance
“…The symbolic association driving a brand choice can send significantly meaningful signals to other consumers about the type of person using that brand (Kapferer and Bastien 2009;Han et al 2010;Berger and Ward 2010). It is widely accepted that people make inferences about others, based on their choices of consumption objects (Belk 1988).…”
Section: Symbolic Valuementioning
confidence: 99%
See 2 more Smart Citations
“…The symbolic association driving a brand choice can send significantly meaningful signals to other consumers about the type of person using that brand (Kapferer and Bastien 2009;Han et al 2010;Berger and Ward 2010). It is widely accepted that people make inferences about others, based on their choices of consumption objects (Belk 1988).…”
Section: Symbolic Valuementioning
confidence: 99%
“…Additionally, it has been observed that consumers in the developed Western markets use their symbolic possessions such as luxury brands to extend, expand and strengthen their sense of self (Belk 1988;Kapferer and Bastien 2009). Using the context of privately consumed inconspicuous food products, Zhou and Hui (2003) find the increasing importance of self-directed symbolism among Chinese consumers.…”
Section: Symbolic Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Some brands are viewed as cheap and in expensive, while others are viewed as a better quality and expensive Kapferer [8]. In their research, Cervellon & Shammas [1] show that luxury brands these days are complimentary with sustainability through ethos (e.g., eco-brands such as Stella McCartney (Kering/PPR) or Edun (LVMH) in luxury fashion or Tesla Roadsters and Venturi luxury cars), commitment all along the supply chain (Gucci group,LVMH, Porsche) and/or introduction of eco-collection and eco-lines (BMWi3 electric cars, Vranken-Pommery Pop Earth Champagne, Issey Miyake 132.5 origami design collection, Gucci sunglasses made out of liquid wood produced from sustainably managed forests).…”
Section: Introductionmentioning
confidence: 99%
“…O papel da propaganda, por exemplo, não é necessariamente estimular a venda direta para o público em geral, mas sim tentar estimular o desejo, tanto dentro quanto fora de seu target (Kapferer & Bastien, 2009a;Kapferer & Vincent, 2009b;Kapferer & Valette Florence, 2016).…”
Section: Introductionunclassified